The role of the principal as a leader, innovator and motivator in vocational high schools - Nellitawati Nellitawati; Ermita Ermita (Journal of Educational and Learning Studies, 2021)
As a leader, a school principal has several roles that are needed in improving the quality of education in the school. This study aims to analyze the role of school principals in leading teachers. This research method is quantitative research. The population in this study was 865 teachers at Vocational High school. The sampling technique is Cluster Random Sampling. Data analyzed used descriptive quantitative data. Instrumen tha t used were Principal as Leader Scale. The results of the study stated that the role of the principal has been good. The role is good as a leader, innovator and motivator. To improve the quality of education, it is still necessary to increase the role of the principal in leading, providing innovation, and as a motivator.